1991
DOI: 10.1073/pnas.88.13.5597
|View full text |Cite
|
Sign up to set email alerts
|

Expression and enzymatic activity of recombinant cytochrome P450 17 alpha-hydroxylase in Escherichia coli.

Abstract: When the cDNA encoding bovine microsomal 17a-hydroxylase cytochrome P450 (P45017a) containing modifications within the first seven codons which favor expression in Escherichia coli is placed in a highly regulated tac promoter expression plasmid, as much as 16 mg of spectrally detectable P45017a per liter of culture can be synthesized and integrated into E. coli membranes. The known enzymatic activities of bovine P45017a can be reconstituted by addition of purified rat liver NADPH-cytochrome P450 reductase to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
356
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(367 citation statements)
references
References 30 publications
8
356
0
3
Order By: Relevance
“…The first published was a fusion of rat CYP1A1 and yeast RED 22 and was expressed in yeast. Since then several groups have constructed fusion proteins including human CYP3A4 fused to rat RED 21 and expressed them in bacteria 24,25,41 for functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…The first published was a fusion of rat CYP1A1 and yeast RED 22 and was expressed in yeast. Since then several groups have constructed fusion proteins including human CYP3A4 fused to rat RED 21 and expressed them in bacteria 24,25,41 for functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…We detected little or no protein in strain M15 which is recommended for pQE-6 derivatives, or in the strains DH5cz and JM109 which have been used successfully for the expression of animal P450 alone or as PasdP450-RED fusions (see [11,13] for some examples). Those experiments revealed unexplained differences between DHScz and JM 109 as well, and we have no simple explanation for the finding that the C4H/ P,50-RED expression was successful in DS410, but not in the others.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons may be that these bacteria lack P450 activities [1] and thus also the characteristic cytochrome P4s0 reductase (P45o-RED) that is necessary for P45o function. Results with some animal P450 suggested that it may be replaced by the combined action of two soluble E. coli flavoproteins [10,11], but a high efficiency required purified proteins [12], and the general applicability was not investigated. The obtaining of active P450 then requires the reconstitution with purified plant P450 reductase, but that is technically tedious and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…However, taking the lead from numerous groups that have focused on E. coli gene expression of mammalian and plant P450 enzymes (Barnes 1996;Barnes et al 1991;Chang et al 2007;Leonard et al 2006;Pritchard et al 2006;Yun et al 2006), functional expression of the first Taxol pathway P450 was accomplished (Ajikumar et al 2010). Doing so required truncation of the native transmembrane region (with three different truncation lengths tested) and further modification of the N-terminal portion of the enzyme to include an eight amino acid membrane anchor peptide sequence (MALLLAVF) which has proven functional in E. coli (Barnes et al 1991). Furthermore, as in the case of the taxadiene synthase, the P450 gene was synthesized to eliminate any codon bias (this same step was also taken for the accompanying P450 reductase), and reduced temperature induction conditions and other process parameters were modified so as to maximize eventual production (Table 1).…”
Section: Challenges and Options Associated With The Heterologous Implmentioning
confidence: 99%
“…This can be mitigated by the native capabilities to complement reductase activity when using S. cerevisiae, but the same level of convenience may not be provided with E. coli (Barnes et al 1991;Jennewein et al 2005;Oeda et al 1985). Again thanks to work by Rodney Croteau's group, a reductase has been isolated from Taxus cuspidata (Jennewein et al 2005).…”
Section: Challenges and Options Associated With The Heterologous Implmentioning
confidence: 99%